PERIPAPILLARY NEUROVASCULAR COUPLING IN THE EARLY STAGES OF DIABETIC RETINOPATHY. Issue 12 (December 2019) - Rodrigues, Tiago M.; Marques, João P.; Soares, Mário; Dolan, Michael-John; Melo, Pedro; Simão, Sílvia; Teles, João; Figueira, João; Murta, Joaquim N.; Silva, Rufino
Abstract : Purpose: To study radial peripapillary capillary (RPC) density in the early stages of diabetic retinopathy (DR), using optical coherence tomography angiography. Methods: A cross-sectional evaluation of RPCs was performed using optical coherence tomography angiography (Avanti RTVue-XR 100, Optovue Inc, Fremont, CA). Annular RPC density was the primary outcome. Global density and retinal nerve fiber layer thickness were secondary outcomes. Diabetic eyes were divided into three groups: no DR, mild nonproliferative DR (mild NPDR), and moderate NPDR. Multilevel mixed-effects univariate and multivariate linear regression models were used. Results: We included 155 eyes (n = 42 control; n = 27 no DR; n = 28 mild NPDR; and n = 58 moderate NPDR) from 86 subjects (mean [SD] age 63.39 [10.70] years; 46.45% male). When compared with controls, a significant decrease in annular RPC density was found in all groups of diabetic eyes on multivariate analysis (no DR: β = −2.95, P < 0.001; mild NPDR: β = −1.76, P = 0.017; and moderate NPDR: β = −2.82, P < 0.001). We also detected a significant decrease in retinal nerve fiber layer thickness in diabetic eyes (even in the no DR group). Furthermore, in diabetic eyes, annular RPC density and retinal nerve fiber layer thickness correlated significantly (R = 0.4874, P < 0.001). Conclusion: Peripapillary neurovascular changes occur early in the course of DR. Their significance in the progression of DR warrants further research. Abstract : Supplemental Digital Content is Available in the Text.This cross-sectional, prospectively defined, observational study demonstrates that the density of perfused peripapillary capillaries, evaluated with optical coherence tomography angiography, is decreased in eyes of diabetic patients with early diabetic retinopathy, but also when clinical signs of retinopathy were absent. Peripapillary vascular changes may occur early in disease progression.